PENGEMBANGAN INVOVASI PENDIDIKAN KOMUNIKASI MULTIKULTURAL MELALUI TAYANGAN RAGAM INDONESIA SEBAGAI STATEGI PENGUATAN IDENTITAS NASIONAL - Eko Digdoyo (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2018)
The content of television as a public media broadcasts generally present news or social reality eventsyet it seems to be appropriate that the content must be received wisely andcritically. Receiving information without discretion will create a wrong and misleading image of the world, including an overview of multicultural education. Currently, mass media has a significant potential to instill prejudice between religions, cultures, and so on. The media in this case also has social responsibility to the public about the issues of freedom and protection of multicultural educationunderstanding. Therefore to support the theoretical approachof this study, theory about value of multicultural education whichisreinforcedby theory of social media responsibility was taken into account. The results showed thatRagam Indonesia as one of the television programs in Indonesia (in Trans 7) has been presenting shows that could be used as a good start to develop innovations in multicultural communication education, given the impressions of the content in Ragam Indonesia including the aspects of life; economics, religion, tradition, as well as local identities that can be wrapped into national identities as learning material for students, college students, and society. This kind of publication is considered to be very urgent in order to build national identity.Key words: Inovation, Multicultural Education, Media, and National Identity